Economic implications of the Divergence Indicators in the EMS - Wolfgang Filc (Intereconomics, 1979)
The system of so-called Divergence Indicators in the European Monetary System puts pressure on the monetary authorities to consult before the intervention points are reached in the foreign exchange markets. Under integration aspects this arrangement marks an advance, but it also carries risks and dangers with it.
Keywords: 330; European Monetary System